The effect of pro-inflammatory conditions on iron homeostasis and atherogenesis - Marques, Liliana (2013)
This work was supported by National Institute of Health Dr Ricardo Jorge, I.P, INSERM (Institut National de la Santé et de la Recherche Médicale), CNRS (Centre National de la Recherche Scientifique), ANR (Agence Nationale de la Recherche, France; ANR- 08-GENO-000) , Fundação para a Ciência e Tecnologia (Grant SFRH/BD/48671/2008) and BioFIG (B Center for Biodiversity, Functional and Integrative Genomics).